Standardization or Adaptation in Cosmetics Websites Marketing? An Empirical Study - Anca Constantinescu-Dobra (CES Working Papers, 2011)
The websites marketing is becoming an important tool both for multinationals and SMEs, in their effort to internationalizing their business. This study focuses on the international opportunities that are present within the European markets. The paper aims at identifying the degree of websites marketing standardization vs. adaptation, as a marketing tool for cosmetic products. Moreover, the study examines in a comparative manner the standardization strategy of multinationals and small and medium enterprises (SMEs), leaders in European markets, for different cosmetic cathegories. The evaluation of online advertising standardization is based on the modified Model for Testing Advertising Standardization, developed by Whitelock and Chung. The web sites degree of localizations are analyzed based upon 98 criteria, as resulted from an adapted methodology of ProfNet Institut fur Internet Marketing, Munster (Germany). The sample includes the 101 leaders from European markets. The research outcomes reflect a standardized websites marketing policy for SMEs and localized for multinationals. Also, for perfumes, dental care products and toiletry, European cosmetic leaders implement standardized websites marketing policies and balanced for the other cosmetics categories. The hypothesis concerning a strong correlation between standardization and handling dimension was supported.
Keywords: 330; websites marketing; SME; multinationals; online interactivity; cosmetics; standardization; adaptation Romania